Slow Sand Filter untuk Pengolahan Air di Desa Pekauman Ulu, Kalimantan Selatan - Nafisah Nafisah; Nafia Fitrawati; Risaldi Ridwan; Fathul Jannah; Puspita Jamilah Rahimah; Utami Irawati (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Pekauman Ulu Village is one of the villages crossed by the Martapura river, where the water is used by  the people of this village for their daily activities. Pekauman Ulu Village is a densely populated area which is flooded every year. The water is very turbid with an unpleasant smell,  and consuming this water often makes some people get diarrhea. Thus, a simple technology is needed to treat this river water into clean water. This activity aims to build  Slow Sand Filter (SSF) units as a means of providing clean water for people in Pekauman Ulu Village. The activity is conducted in three parts: initial dissemination, training, and evaluation. Based on the survey done to the people joining the training, 95.25% of the people said that they were satisfied with the water being treated by SSF. As for the performance of the SSF itself, turbidity measurement of water samples showed that the turbidity of water filtered by the SSF unit reduced from an average of 41.7 NTU to 2.3 NTU.  It can be concluded that this community development program has successfully addressed the need for clean water for people in Pekauman Ulu Village.